Bulk observables at 5.02 TeV using quasiparticle anisotropic hydrodynamics - Mubarak Alqahtani (SpringerOpen, 2021)
Abstract We compare predictions of 3+1D quasiparticle anisotropic hydrodynamics (aHydroQP) for a large set of bulk observables with experimental data collected in 5.02 TeV Pb–Pb collisions. We make predictions for identified hadron spectra, identified hadron average transverse momentum, charged particle multiplicity as a function of pseudorapidity, the kaon-to-pion ( $$K/\pi $$ K / π ) and proton-to-pion ( $$p/\pi $$ p / π ) ratios, identified particle and charged particle elliptic flow, and HBT radii. We compare to data collected by the ALICE collaboration in 5.02 TeV Pb–Pb collisions. We find that, based on available data, these bulk observables are well described by aHydroQP with an assumed initial central temperature of $$T_0=630$$ T 0 = 630  MeV at $$\tau _0 = 0.25$$ τ 0 = 0.25 fm/c and a constant specific shear viscosity of $$\eta /s=0.159$$ η / s = 0.159 , which corresponds to a peak specific bulk viscosity of $$\zeta /s = 0.048$$ ζ / s = 0.048 . In particular, we find that the momentum dependence of the kaon-to-pion ( $$K/\pi $$ K / π ) and proton-to-pion ( $$p/\pi $$ p / π ) ratios reported recently by the ALICE collaboration are extremely well described by aHydroQP in the 0–5% centrality class.